1996
DOI: 10.1093/ajcp/105.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma in Cirrhotic and Noncirrhotic Livers:A Clinico-Histopathologic Study of 804 North American Patients

Abstract: This study examined clinico-histopathologic differences between North American patients who developed hepatocellular carcinoma with and without cirrhosis.Histologic slides and clinical records of cases were reviewed. Cases were classified according to defined histopathologic criteria. Analyses were performed using appropriate tests.A total of 42.6% of cases were noncirrhotic. The trabecular type of hepatocellular carcinoma was the most common growth pattern in both groups. Patients with cirrhosis were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
3
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(126 citation statements)
references
References 25 publications
6
112
3
5
Order By: Relevance
“…In a previous study, 11 HCC was identified in 19% of alcoholic liver disease patients without evident cirrhosis. In another study, 12 14% of alcoholics with HCC did not have cirrhosis.…”
Section: Introductionmentioning
confidence: 83%
“…In a previous study, 11 HCC was identified in 19% of alcoholic liver disease patients without evident cirrhosis. In another study, 12 14% of alcoholics with HCC did not have cirrhosis.…”
Section: Introductionmentioning
confidence: 83%
“…[30][31][32] Survival advantages of hepatocellular carcinomas arising from noncirrhotic liver over hepatocellular carcinomas arising from cirrhotic liver have been well documented. [33][34][35] This survival difference is believed to be because of the poor liver functional reserve in cirrhotic liver and the tendency towards development of a new primary after surgery. 36,37 However, it is yet unknown whether there is any effect of cirrhosis on the metastatic potential of hepatocellular carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…[71][72][73] This figure is in line with the results of a few small UK series from the 1980s, in which rates of 73-80% were reported, [74][75][76] and comparable with data from elsewhere in Europe (71-88% in France, [77][78][79][80] 75-90% in Germany, [81][82][83][84][85] 77-97% in Italy [86][87][88][89][90][91][92] and 93% in Spain 93 ). The picture may be different in North America, where similar studies suggest that the proportion of HCC patients who have cirrhosis is as low as 58% 94 to 63%. 95 The rate at which cirrhotic livers progress to HCC is one of the key topics under review in the present study, and is addressed in detail below.…”
Section: Aetiologymentioning
confidence: 98%